Effectiveness of social media as a marketing communication tool in Tanzania - Odhiambo, Luis (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment of the requirements for the award of Master’s Degree of Business Administration (MBA) of Mzumbe University